The Consonant System of the English Language and its Modification in Colloquial Speech - Poladova, Sabina Elkhan (Advances in Social Sciences Research Journal, 2021)
This paper is concerned with the study of the modifications of consonants caused by their mutual influence, taking into account the varying degrees of connectivity of the elements of the speech chain. As such, this study of vocal connections of various types is carried out from the point of view of the nature of the junction of the elements – more or less close. Thus, this paper is devoted to problems concerning the phenomenon of vocal junction as it is established in linguistics in general and in phonetics in particular. The relevance of these problems stems from the need for disclosure and knowledge of the mechanism of internal organization of speech flow. This paper is aimed at analyzing the features of the vocal stitch and its components, which allow you to delve deeper into the mechanism of production of related speech. Thereby, this study attempts to identify modifications of elements of interdisciplinary vocal combinations, which are important for the implementation of their delimitative function, as these are manifested in the distinction of different units of speech.